Regaining Control Over our Genes: Energy, Vibration, and Tibetan Singing Bowl Therapy - Matei, Alexandra (New Trends in Psychology, 2024)
Our thought systems, positive intentions, and vibrations expressed through sound, writing, and other forms, along with an individual's will to shape their life, constitute key elements in their micro-universe and consciousness. Changes at this level offer a holistic understanding of the individual and their experiences, influencing life quality emotionally, socially, economically, and spiritually. This bidirectional interaction between the biological system and human capacity for transformation through consciousness and belief remains a mystery for researchers and cognitive psychology. The paper explores how our thoughts' vibrations can cause radical changes in the human body, thus improving or not improving life quality. Although this hypothesis cannot be statistically quantified due to limited resources, I will use my own experimental observation gained from providing sound healing treatments in analyzing the hypothesis. Based on my clients' responses and specialized literature, an improvement in the emotional and biological state of individuals who underwent the procedure was observed.